One‐Pot Multicomponent Reaction: A Highly Versatile Strategy for the Construction of Valuable Nitrogen‐Containing Heterocycles. Issue 33 (1st September 2022) - Nandi, Sibaji; Jamatia, Ramen; Sarkar, Rajib; Sarkar, Fillip Kumar; Alam, Safiul; Pal, Amarta Kumar
Abstract: A large portion of the chemical subspace is the multi‐component reaction (MCR). Apart from Domino reactions, MCR is one of the most promising routes for one‐pot synthesis. Thus, MCR derived product can be considered as a synthetic hub to a vast diversity of novel cyclic or acyclic compounds. Heterocyclic moiety such as naphthyridines, quinolines, dihydropyridines (DHPs), quinazolines, pyrimidines, imidazoles, diazepines, and spiro‐heterocycles are widely recognized in clinical evaluation. Because of their relevant significance, vast literature exists to accomplish the synthesis of these biologically important compounds. Therefore, this review highlights the last ten years of developments in the one‐pot synthesis of these heterocyclic moieties which are widely recognized by the industry in addition to academia. Abstract : Heterocyclic N ‐containing moieties are highly valuable and widely recognized in modern organic chemistry. This sparks the interest of researchers in the development of strategies involved in their synthesis. We envisioned that this literature review will provide the readers with an in‐depth understanding of the various multicomponent strategies employed for the synthesis of these heterocycles.